Active controller for an upper extremity exoskeleton using EMG feedback - Manguerra, Michael V. (Animo Repository, 2017)
An active control system for a 5-DOF upper limb robotic exoskeleton was developed to fill in the need for an accessible and cost-effective rehabilitation system. Since physical therapy sessions are labor intensive, it aims to be a tool in augmenting the capacity of local rehabilitation centers in catering more patients. Many different control systems were already done on similar devices but the challenges remain in adapting to the limits of the mechanical design of the exoskeleton it is implemented on and availability of local electronic components. The rectified EMG Signal was further smoothened thru Running Average. Trials were done on a healthy subject due to limited access to stroke patients. Target muscles are Biceps and Triceps for Elbow Flexion and Extension; Deltoids and Teres Major for Shoulder Abduction and Adduction. Experimental results showed that baseline EMG and activation level of the target muscle groups are different from each other, thus different threshold levels were established. An adaptive algorithm was also implemented in varying the supplied power depending on the applied load on the arm. Stall conditions via the current sensor was monitored and used as positive feedback. The system was successful in interpreting intent to move and translating it to motor movement. System was evaluated and validated via consultations with medical collaborators from PGH Department of Rehabilitation Medicine. As part of Project AGAPAY, under the guidance of the Philippine Biomedical Device Innovation Consortium (BIOMEDIC PH), this thesis aims to be a benchmark in rehabilitation robotics here in the Philippines.